Fast-Tunable Terahertz Metamaterial Absorber Based on Polymer Network Liquid Crystal - Zhiping Yin; Chaofan Wan; Guangsheng Deng; Andong Zheng; Peng Wang; Yang Yang; Sheng Gao; Jun Yang; Fei Cai; Zelun Li; Hongbo Lu (Applied Sciences, 2018)
This paper introduces a tunable metamaterial absorber (MA) based on polymer network liquid crystal (PNLC) in the terahertz (THz) frequency band. Under the optimal polymerization condition, through electrical control of the orientation of the PNLC embedded in the frequency selective surface, the resonant frequency of the absorber can be tuned from 416.5 to 405.0 GHz, corresponding to fractional frequency bandwidth of 2.8%. The experimental results show that the proposed MA based on the PNLC offers an adjustment time of 10 ms and recovery time of 85 ms, which is significantly faster than the tunable metamaterial devices based on conventional nematic liquid crystal (LC).